Reply to the 'Comment on Cage occupancy of methane clathrate hydrates in the ternary H2O–NH3–CH4 system' by S. Alavi and J. Ripmeester, Chem. Commun., 2022, 58, DOI: ; 10.1039/D1CC06526B. Issue 25 (15th March 2022) - Choukroun, Mathieu; Petuya, Claire; Vu, Tuan H.; Desmedt, Arnaud; Davies, Ashley Gerard; Sotin, Christophe
Abstract : Our recent Communication suggested that ammonia in aqueous solution may preferentially destabilize large cages in methane clathrate hydrates. Abstract : Our recent Communication suggested that ammonia in aqueous solution may preferentially destabilize large cages in methane clathrate hydrates. A Comment favored ammonia incorporation instead, but it did not accurately describe our proposed mechanism and relied primarily on studies conducted in different chemical systems and/or which used other preparation methods.